Die Rolle der katholischen Kirche Polens in der Nachkriegszeit - Sauerland, Karol (Kirchliche Zeitgeschichte, 2007)
This essay describes developments in the Catholic church in post-war Poland. The author shows the failure of the attempts by the new Communist rulers after 1949 to repress the church by draconian measures. In fact, such attacks only led to the institution's unprecedented strength. An important contribution came from those opposition forces who were more or less atheists, at least until the mid-1970s. Later they came to recognize that any repression of the faithful church-goers was incompatible with democratic social goals. The author describes the clever tactics adopted by the Polish Cardinal Wyszynski as well as by the Polish Pope John Paul II in their dealings with the Communist authorities.